Two-photon vision in age-related macular degeneration: a translational study - Łabuz, Grzegorz; Zielińska, Agnieszka; Kessler, Lucy Joanne; Rayamajhi, Asu; Komar, Katarzyna; Khoramnia, Ramin; Auffarth, Gerd U. (Diagnostics, 2022)
The recently introduced term “two-photon vision” relates to the visual perception resulting from a simultaneous absorption of two photons by photoreceptors. In this study, we determined two-photon retinal sensitivity in age-related macular degeneration (AMD) and compared it that in normal aging. Microperimetry was performed with visible (white) light and infrared (IR) light, which was perceived as green in the two-photon stimulation. In total, 45 subjects were included with one (better) eye studied. Furthermore, best-corrected visual acuity (VA) and ocular straylight were assessed. AMD resulted in decreased median (interquartile range) logMAR VA, i.e., 0.15 (0.05; 0.24), which in normal eyes was −0.02 (−0.06; 0.02). The two groups showed comparable straylight levels. Sensitivity to IR light was significantly lower in the AMD group (p < 0.001): 8.3 (7.4, 9.3) dB than in controls 10.7 (9.7, 11.2) dB. AMD also significantly affected visible light sensitivity (p < 0.001): 14.0 (11.0; 15.5) dB vs. 18.0 (16.3; 18.9) dB. Notably, the two-photon approach yielded a lower data spread. In conclusion, AMD considerably impairs retinal sensitivity measured in the single- and two-photon realm. However, two-photon-vision microperimetry may improve the testing accuracy and offer an additional diagnostic parameter (beyond VA measurements) for retinal function assessment.